The consequence of earnings management through discretionary accruals on the value relevance in Saudi Arabia - Basiem Khalil Al-Shattarat (Cogent Business & Management, 2021)
This study explores the relationship between company earnings management and the relative value relevance of book value and earnings. The differential effect on the value relevance of earnings management (EM) from 2014 to 2018 for all firms listed on the Saudi Stock Exchange (Tadawul) is investigated by short-term versus long-term discretionary accruals. For firms whose EM is considered as an indication of its discretionary accruals, it is anticipated that earnings' value relevance would be lower than firms that do not consider EM. The results show that EM discretionary accruals influence the value relevance of book value and earnings for the long-term compared to the short-term. The study's finding is expected to shed light on applying the quality of firms' financial reporting in protecting stakeholders' interests by providing them with credible information free from earnings manipulations.
Keywords: 650; value relevance; earnings management; book value; short-term and long-term discretionary accruals